ANALYSIS OF COST OF GOODS PRODUCED AND VALUE-ADDED AT UMKM TEMPE "TROSOBO" TUBAN - Fitri, Saidatul; Widayanti, Sri; Atasa, Dita (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
Soybeans are a food commodity that contains high vegetable protein and is generally used for food consumption. To meet the demand for tempeh agroindustry that uses soybeans as the primary raw material, agroindustry players increase soybean production. However, they still need to meet this demand. Therefore, the government meets this demand by importing. The research was conducted at UMKM Tempe Trosobo, located in Jl. Brawijaya, Gang Yudistira No. 641, Kebonsari, Kec. Tuban, Kab. Tuban, East Java. This study aims to calculate the cost of goods produced using the Full Costing method and analyze the added Value generated by UMKM Tempe "Trosobo" Tuban from soybean processing. The methods used are the Full Costing method and the Hayami method. The results showed that the calculation of the cost of goods produced in the temple agroindustry of Tempe Trosobo UMKM using the complete costing method was IDR 4,300/piece with the total production of tempe produced as many as 22,500 pieces, and the selling price was IDR 5,100/piece. Processing soybeans into tempeh has a value-added result of IDR 11,925 / kg of raw material or 49%, and the added Value of tempeh is classified as high